The Iron Fist in the Latex Glove: The Intersection of Public Health and Criminal Justice - Potter, Roberto Hugh (American journal of criminal justice, 2013)
The intersection of public health and criminal justice involves reducing negative human outcomes, disease and crime, respectively. In this article, we examine the public health approach in detail and how it relates to criminal justice research and practice and how each discipline achieves legitimacy. We demonstrate the public duties of the criminal justice system and how it already performs some public health duties and how we can better integrate public health approaches at the academic, bureaucratic, and street levels.